Performance analysis of sub‐optimal transmit and receive antenna selection amplify and forward cooperative communication. Issue 20 (1st December 2019) - Bouteggui, Mokhtar; Merazka, Fatiha
Abstract : In this study, the authors consider a multiple‐input–multiple‐output cooperative communication system, based on a single amplify‐and‐forward relay over a Rayleigh fading channel. They investigate the performance of two sub‐optimal transmit receive antenna selection (TRAS) schemes employing M ‐ary phase shift keying ( M ‐PSK). They take the advantages of the moment generating function expression, to avoid the hypergeometric functions commonly used in literature. They derive analytical expressions for the symbol error rate (SER) based on two upper bounds of the instantaneous end‐to‐end signal‐to‐noise ratio (SNR), which are tightly lower bounded for the SER. In addition, an SER upper bound is derived for both TRAS strategies which gets tighter at high SNR. This upper bound is used to determine the system optimal power allocation. Diversity orders for both TRAS strategies are extracted. Their theoretical analysis shows that the SNR upper bound I is tighter compared to the SNR upper bound II especially for sub‐optimal strategy I. At high SNR, the derived SER upper bound approaches the derived SER. Interestingly, it is observed that the optimal power factors lead to a lower SER. Simulation results are presented in comparison with the derived SER for the two upper bounds.